2016
DOI: 10.1080/07315724.2015.1060875
|View full text |Cite
|
Sign up to set email alerts
|

Heme Iron Concentrate and Iron Sulfate Added to Chocolate Biscuits: Effects on Hematological Indices of Mexican Schoolchildren

Abstract: Heme iron concentrate and iron sulfate were equally effective in increasing Hb levels and hematological indices. Processed foods were shown to be an effective, valuable, and admissible intervention to prevent anemia in preschool children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…This may be due to the fact that participants may have increased their intake of Fe-containing foods after being informed of their Fe-deficient status following screening but before they commenced the study. Despite reduction in the placebo group, the present study also demonstrated the effectiveness of Fe-fortified breakfast cereal (irrespective of vitamin D intervention) on raising principal Fe biomarkers which is in agreement with the recent findings ( 31 34 ) .…”
Section: Discussionsupporting
confidence: 93%
“…This may be due to the fact that participants may have increased their intake of Fe-containing foods after being informed of their Fe-deficient status following screening but before they commenced the study. Despite reduction in the placebo group, the present study also demonstrated the effectiveness of Fe-fortified breakfast cereal (irrespective of vitamin D intervention) on raising principal Fe biomarkers which is in agreement with the recent findings ( 31 34 ) .…”
Section: Discussionsupporting
confidence: 93%
“…Hemin is an anti-inflammatory agent with antioxidant effects. It improves anemia, suppresses pulmonary hypertension [ 11 , 12 , 13 , 14 ], and accelerates wound healing in diabetic rats [ 15 ]. In a previous study, we observed peroxidase activity of ferrous hemoglobin that catalyzed the reaction of hydrogen peroxide with tyrosine.…”
Section: Introductionmentioning
confidence: 99%
“…When heme iron was used to fortify foods, it resulted in lipid oxidation like many nonheme fortificants [132]. Despite these challenges, biscuits fortified with heme iron have been shown to be equally as effective as biscuits fortified with FeSO4 in increasing hemoglobin in preschool aged children when fed for 10 weeks [133]. Additionally, chocolate flavored biscuits fortified with heme have been reported to be well accepted by adolescent girls and were effective at raising hemoglobin when fed for 13 weeks [134].…”
Section: Heme and Organic Fortificantsmentioning
confidence: 99%